PARAMETERS OF THE RATIONAL USE OF HORIZONTAL FRAMES OF THE METALLIC CYLINDRICAL RETICULATED COVERAGES - Siianov, O. I. (Visnyk of Vinnytsia Politechnical Institute, 2014)
The parameters of the rational use of horizontal frames of the metallic cylindrical reticulated coverings are found. The change of arrow of raising, implementation of terms of the maximum states and limits is taken into account on the charges of materials. Characteristic conformities to law of work of vulnerable areas of coverings are got. Features of critical deformation of the supported constructions are brought on results of the possible exceeding of the calculation loading.